Relationship between cell concentration and Salmonella attachment to plant cell walls - Sze-Fan Tan, M.; Rahman, S.; Dykes, Gary (Pergamon, 2016)
© 2016 Elsevier Ltd. Cut surfaces of fresh produce, which directly expose plant cell walls to the environment, are particularly susceptible to contamination by pathogens, including Salmonella enterica. The effect of Salmonella cell concentration in liquids (such as rinses or washes) on their attachment to plant cell walls was investigated using bacterial cellulose-based plant cell wall models. Numbers of Salmonella cells attaching to the plant cell wall models increased linearly with cell concentration. A simple linear model (y = 0.916x) was constructed to predict the number of Salmonella cells that will attach to per unit surface area of plant cell wall (CFU/cm2), assuming their initial inoculum concentration lies within the range of 3 log to 8 log CFU/mL. The linear regression model generated from the model surfaces was validated for a range of variables (different plant tissues, S. enterica subspecies and other foodborne bacteria). The validation supported the use of the linear regression model in predicting Salmonella attachment to plant cell walls regardless of the Salmonella subspecies. The use of the model can also be extended to other bacteria within the cell concentration range. This work may contribute to generating risk-assessment tools for control of Salmonella associated with the processing of fresh produce.